Papers of C.S. Hertz - Hertz, C. S. (Cyril Sidney), -1980. (1877)
The MS 9090 collection mainly comprises Australian and British newspapers and newspaper cuttings relating to World War I and II. Included are newspapers dating from 1917-1945, reprints of historical issues and papers containing articles on historical subjects, 1962-1973. In addition, files maintained by Hertz containing correspondence; drafts of articles by Hertz; Fifth Australian Infantry Brigade operation orders, reports on operations and other records, 1917-1920; extracts from publications, articles, casualty lists, unit histories and other military research materials; papers relating to Hertz's membership of the Freemasons, a menu for the visit of General Ulysses S. Grant to London, 15 June 1877; and ephemera relating to a public reception for the Prince of Wales, Town Hall, Sydney, 18 June, 1920 (3 boxes).
The Acc09/95 instalment includes stamps commemorating the 50th anniversary in 1969 of the first England-Australia flight; typescript explanation and stamps commemorating fifty years of air mail in Australia; and three booklets on aviation themes (1 folder).
Manuscript reference no.: MS 9090, MS Acc09.095.
National Library of Australia Pictures collection PIC/11428.
National Library of Australia Map collection, MAP/Hertz Special Col/ 1-71
Cyril Sidney Hertz was a collector of books, maps and other material on the military and aviation history of the First and Second World Wars.
Exhibited: "Keepsakes: Australians and the Great War", National Library of Australia, 26 November 2014 - 19 July 2015
Keywords: Hertz, C. S. -- -1980 -- Archives; Hertz, C. S. -- -1980 -- Stamp collections; Australia. -- Army. -- Infantry Brigade, 5th.; Book collectors -- Australia -- Archives; World War, 1914-1918.; World War, 1939-1945.; Book collectors